Understanding and Offering Solutions to Cases of Victims of Covid-19 Vaccination in Indonesia (Legal Literacy Review Study) - Gunawan Widjaja (Budapest International Research and Critics University, 2021)
This paper aimed to understand and provide solutions to several victims of Covid vaccination in Indonesia, which are the topic of news and the issue of National vaccination by the government to the citizens. To expedite the discussion of this topic, the author has successfully carried out a series of electronic data collection in many publications such as health journals, both national and international, both on mass media, social media, and discussed how the implementation of vaccination runs smoothly, safely and fairly. So, the following process of this paper involved data analysis methods, including coding systems, non-in-depth data evaluation, so that the author can conclude the final data as findings to answer this study problem with valid and reliable findings. Before presenting the case, first, we also get a core understanding of the topic of discussion about Covid-19 and cases of vaccination failure, and finally, we try to offer a solution which we believe is that the solution will provide a sense of justice for the restoration of the rights to safety and health for the people who are victims of the national vaccine program.